The Effectiveness of Visual Literacy in Developing Environmental Character of Grade IV Students of SDN 3 Rantepao - Regina Li’pang; Dina Gasong; Rita Tanduk (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study was motivated by the weak character of environmental love in elementary school students. This can be seen from the low concern for classroom cleanliness, waste management, and a lack of understanding of the importance of preserving the environment. This study aims to determine the effectiveness of visual literacy in forming and developing the character of environmental love in grade IV students at SDN 3 Rantepao. The method used is quantitative research with a quasi-experimental approach involving two classes, namely the experimental class and the control class. Data were collected through observation, interviews, and questionnaires. The results of the study showed that the application of visual literacy media such as environmental posters, infographics, and educational videos significantly increased students' awareness and behavior of environmental love. The main contribution of this study is to prove that visual literacy is not only a means of conveying information but also effective in forming students' character through an attractive and easy-to-understand visual approach. This study recommends the use of visual literacy as part of a character education learning strategy, especially the character of caring for the environment from an early age. The main contribution of this study is to prove that visual literacy is not only a means of conveying information, but also effective in shaping students' character through an attractive and easy-to-understand visual approach, which has been proven to increase the average knowledge about the environment by 26%, environmental care attitudes by 18%, and real actions in protecting the environment by 26% in students.